Rescuing ESAT-6 Specific CD4 T Cells From Terminal Differentiation Is Critical for Long-Term Control of Murine Mtb Infection - Clemmensen, Helena Strand; Knudsen, Niels Peter Hell; Billeskov, Rolf; Rosenkrands, Ida; Jungersen, Gregers; Aagaard, Claus; Andersen, Peter; Mortensen, Rasmus (Frontiers in Immunology, 2020)
In most cases, Mycobacterium tuberculosis (Mtb) causes life-long chronic infections, which poses unique challenges for the immune system. Most of the current tuberculosis (TB) subunit vaccines incorporate immunodominant antigens and at this point, it is poorly understood how the CD4 T cell subsets recognizing these antigens are affected during long-term infection. Very little is known about the requirements for sustainable vaccine protection against TB. To explore this, we screened 62 human-recognized Mtb antigens during chronic murine Mtb infection and identified the four most immunodominant antigens in this setting (MPT70, Rv3020c, and Rv3019c and ESAT-6). Combined into a subunit vaccine, this fusion protein induced robust protection both in a standard short-term model and in a long-term infection model where immunity from BCG waned. Importantly, replacement of ESAT-6 with another ESAT-6-family antigen, Rv1198, led to similar short-term protection but a complete loss of bacterial control during chronic infection. This observation was further underscored, as the ESAT-6 containing vaccine mediated sustainable protection in a model of post-exposure vaccination, where the ESAT-6-replacement vaccine did not. An individual comparison of the CD4 T cell responses during Mtb infection revealed that ESAT-6-specific T cells were more terminally differentiated than the other immunodominant antigens and immunization with the ESAT-6 containing vaccine led to substantially greater reduction in the overall T cell differentiation status. Our data therefore associates long-term bacterial control with the ability of a vaccine to rescue infection-driven CD4T cell differentiation and future TB antigen discovery programs should focus on identifying antigens with the highest accompanying T cell differentiation, like ESAT-6. This also highlights the importance of long-term readouts in both preclinical and clinical studies with TB vaccines.